Kinetics of imidazole propionate from orally delivered histidine in mice and humans - Warmbrunn, Moritz V.; Attaye, Ilias; Horak, Anthony; Banerjee, Rakhee; Massey, William J.; Varadharajan, Venkateshwari; Rampanelli, Elena; Hao, Youling; Dutta, Sumita; Nemet, Ina; Aron-Wisnewsky, Judith; Clément, Karine; et al. (NPJ biofilms and microbiomes, 2024)
Imidazole Propionate (ImP), a gut-derived metabolite from histidine, affects insulin signaling in mice and is elevated in type 2 diabetes (T2D). However, the source of histidine and the role of the gut microbiota remain unclear. We conducted an intervention study in mice and humans, comparing ImP kinetics in mice on a high-fat diet with varying histidine levels and antibiotics, and assessed ImP levels in healthy and T2D subjects with histidine supplementation. Results show that dietary histidine is metabolized to ImP, with antibiotic-induced gut microbiota suppression reducing ImP levels in mice. In contrast, oral histidine supplementation resulted in increases in circulating ImP levels in humans, whereas antibiotic treatment increased ImP levels, which was associated with a bloom of several bacterial genera that have been associated with ImP production, such as Lactobacilli. Our findings highlight the gut microbiota’s crucial role in regulating ImP and the complexity of translating mouse models to humans.